F-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in a Rare Case of Recurrent Malignant Mixed Mullerian Tumor - Bhoil, Amit; Kashyap, Raghava; Bhattacharya, Anish; Mittal, Bhagwant (World Journal of Nuclear Medicine, 2014)
We report a case of 66-year-old female with previous history of histopathologically proven. Malignant mixed mullerain tumor of the uterus in whom positron emission tomography/computed tomography (CT) done for characterization of soft tissue lesion in pelvis noticed on CT, showed extensive recurrent disease in the pelvis with pulmonary metastases.
Keywords: Computed tomography; F-18 fluorodeoxyglucose; malignant mixed mullerian tumor recurrence; positron emission tomography/computed tomography; uterine carcinosarcoma